The Impact of Individual Expertise and Public Information on Group Decision-Making - Strunz, Ulrich G. (FOM-Edition Research, 2021)
In this open-access-book the author concludes that expertise could be the key factor for global and interconnected problems. Experimental results have shown that expertise was a stronger predictor than public information regarding change in behavior and strategy adaption. Identifying non-routine problem-solving experts by efficient online assessments could lead to less volatile system performance, from which all decision-makers could potentially profit.